Pemahaman Masyarakat Tentang Penerapan Akuntansi Pada Usaha Mikro Kecil Dan Menengah (UMKM) - Setiawan, Erik (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
Accounting is a process of recording data obtained from a certain institution which produces reports to interested parties regarding economic activities and company conditions. In today's digital era, many small businesses or (MSMEs) are supporting the nation's economy. Until now, there are still many who have not applied accounting to Micro, Small and Medium Enterprises (MSMEs) and the obstacles they face. This study took 30 MSMEs in the city of Yogyakarta using the questionnaire filling method. The data used in this article's data are primary data that can be obtained by means of interviews and questionnaires. The analysis technique of this research is descriptive qualitative analysis technique. The results showed that most of the MSMEs in Yogyakarta had recorded sales, purchases, supplies, salaries and other expenses. The obstacles for MSMEs in applying accounting include educational background, never having attended accounting training and there is no need for accounting applications.Â